ILP turns 20 - Muggleton, Stephen; De Raedt, Luc; Poole, David; Bratko, Ivan; Flach, Peter; Inoue, Katsumi; Srinivasan, Ashwin (Machine learning, 2012)
Issue Title: Special Issue on Inductive Logic Programming (ILP 2010); Guest Editors: Paolo Frasconi and Francesca A. Lisi Inductive Logic Programming (ILP) is an area of Machine Learning which has now reached its twentieth year. Using the analogy of a human biography this paper recalls the development of the subject from its infancy through childhood and teenage years. We show how in each phase ILP has been characterised by an attempt to extend theory and implementations in tandem with the development of novel and challenging real-world applications. Lastly, by projection we suggest directions for research which will help the subject coming of age.[PUBLICATION ABSTRACT]